CYP2C9 polymorphism: prevalence in healthy and warfarin-treated Malay and Chinese in Malaysia - Ngow, Harris Abdullah; Wan Khairina, Wan Mohd Nowalid; Teh , Lay Kek; Lee, Wee Leng; Harun, Roslan; Ismail, Rusli; Salleh, Mohd Zaki (Singapore Medical Association, 2009)
Introduction: Genetic polymorphisms of CYP2C9 among different populations in different geographical regions could be dif ferent . CYP2C9 has been reported to be the enzyme responsible for the metabolism of many drugs, including warfarin and other drugs with a narrow therapeutic index. Realising the importance of inter-individual differences in the genetic profile in determining the outcome of a drug therapy, this study was conducted to explore the types and frequencies of CYP2C9 alleles in healthy and warfarin-treated Malays and Chinese, the two major ethnic groups in Malaysia. We aimed to evaluate the prevalence of the types and frequencies of common CYP2C9 alleles (*1, *2, *3 and *4) among the healthy unrelated individuals and diseased patients prescribed with warfarin.